Cylindrical antennas and arrays - King, Ronold W. P. (Ronold Wyeth Percival), 1905-2006 (Cambridge University Press, 2002)
This book explains how to design, analyse and test cylindrical antenna arrays from a practical engineering standpoint. Written by three of the leading engineers in the field, this book is destined to become established as the basic reference in the field for many years to come.